1979
DOI: 10.1530/jrf.0.0550087
|View full text |Cite
|
Sign up to set email alerts
|

Ovulation rate and oocyte numbers in ewes after prolonged exposure to oestrogenic pasture

Abstract: Ewes which had been exposed to oestrogenic clover for 3 years showed an elevated ovulation rate but no difference in numbers of primordial follicles compared with normal ewes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The increased LH would stimulate the ovary to secrete more Ez and eventually a new dynamic equilibrium would be set in which higher plasma levels of gonadotrophins and E z were produced. Elevation in gonadotrophin levels would stimulate follicular development, and in support of this Adams et al (1979) have observed higher ovulation rates in ewes that became infertile after grazing oestrogenic clover.…”
Section: Introductionmentioning
confidence: 76%
“…The increased LH would stimulate the ovary to secrete more Ez and eventually a new dynamic equilibrium would be set in which higher plasma levels of gonadotrophins and E z were produced. Elevation in gonadotrophin levels would stimulate follicular development, and in support of this Adams et al (1979) have observed higher ovulation rates in ewes that became infertile after grazing oestrogenic clover.…”
Section: Introductionmentioning
confidence: 76%
“…Laparoscopy was the most common method used to assess whether ovulation had occurred [one outcome per study, with the exceptionof Smith et al ( 114 )]. Four of the studies were conducted in sheep, three of which were conducted in Western Australia ( 7 , 114 , 149 ) and the fourth in Egypt ( 150 ). There was no bias across the included studies (P = 0.8349, Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The duration of oestrous behaviour was not altered in clover-affected ewes (Smith, 1971;Lightfoot et al, 1974). The ovulation rate is slightly higher in clover-affected ewes (Adams, Oldham & Heydon, 1979), and because an increased ovulation rate is generally accompanied by a greater production of oestrogen (Wheeler, Baird, Land & Scaramuzzi, 1977) this may be reflected in a slight increase in the amount of oestrogen circulating in such ewes, although there are no differences in ovarian vein concentrations of oestrogens in affected and control ewes (Rodgers et al, 1980). Taken altogether, the evidence suggests there may be a slight increase in the amount of endogenous oestrogen in affected ewes, but it appears insufficient to cause the large changes seen in cervical mucus (Lindsay & Francis, 1969).…”
Section: Oestrogenmentioning
confidence: 99%